The Disorientation of Value Hierarchies among Generation Z in the Digital Age: A Max Schelerian Analysis - Alfonso Hedo (Kongregasi Hati Kudus Yesus (RSCJ) Indonesia, 2026)
This study aims to analyze the crisis of values, identity, and morality among Generation Z in the digital era through the perspective of Max Scheler’s philosophy of values. The study employs a qualitative approach through a literature review of philosophical works, scholarly articles, and previous studies that discuss Generation Z, digital culture, and Max Scheler’s theory of values. The findings demonstrate that digital culture encourages Generation Z to construct identity through digital recognition, reinforces the phenomenon of Fear of Missing Out (FoMO), and shapes moral orientations that are increasingly influenced by the logic of virality and social validation. From the perspective of Scheler’s hierarchy of values, this condition reflects the dominance of values of pleasure and vital values, while spiritual values and holy values occupy increasingly marginalized positions. As a result, a disorientation of value hierarchy emerges and influences how Generation Z understands the self, social relationships, and moral decision-making within digital spaces. This study expands the application of Max Scheler’s philosophy of values in Generation Z studies and digital sociology by demonstrating the relationship between digital culture, the transformation of value orientations, and moral crises in contemporary society.